Distribution dynamics of nutrient and biomass in yacon organs - Mendes, Tiago Pacheco (2025)
Studies on nutrient absorption patterns allow for the identification of periods of peak nutritional demand, the amount of nutrients accumulated in each organ, the quantity exported by harvest, and the necessary replenishment to the soil. These insights are crucial for developing effective fertilization programs for crops. This study aimed to determine the nutrient absorption pattern of macro and micronutrients and the accumulation of biomass in various organs of yacon plants. The experiment was conducted under field conditions, following a randomized block design. The treatments consisted of different plant ages. Seven evaluations were conducted monthly, starting 30 days after transplanting. Twelve plants from the useful area were sampled for each evaluation. The plants were divided into five parts (leaves, stems, rhizophores, roots, and tuberous roots) to determine dry biomass. The samples were analyzed for N, P, K, Ca, Mg, Cu, Fe, Mn, and Zn content. Yacon prioritized the allocation of photoassimilates for biomass production in the following order: tuberous roots, rhizophores, leaves, stems, and fine roots. Nutrient absorption by yacon plants followed this order: Ca > N > K > Mg > P > Fe > Mn > Zn > Cu. Tuberous roots were the main organ for nutrient accumulated, exporting from the system 71, 15, 57, 125, 11, 1.8, 0.87, 0.40, and 0.27 kg há-1 of N, P, K, Ca, Mg, Fe, Zn, Mn, and Cu, respectively. These results provide critical physiological parameters for formulating evidence-based fertilization programs and modeling yacon growth, thereby advancing precision nutrient management. Moreover, integrating these data into agronomic models and sustainability assessments will facilitate the crop’s development as a high-value functional food, supporting both productive and environmental goals.